Australasian impact crater buried under the Bolaven volcanic field, Southern Laos - Sieh, Kerry (Proc Natl Acad Sci U S A, 2020)
The crater and proximal effects of the largest known young meteorite impact on Earth have eluded discovery for nearly a century. We present 4 lines of evidence that the 0.79-Ma impact crater of the Australasian tektites lies buried beneath lavas of a long-lived, 910-km(3) volcanic field in Southern Laos: 1) Tektite geochemistry implies the presence of young, weathered basalts at the site at the time of the impact. 2) Geologic mapping and (40)Ar-(39)Ar dates confirm that both pre- and postimpact basaltic lavas exist at the proposed impact site and that postimpact basalts wholly cover it. 3) A gravity anomaly there may also reflect the presence of a buried ∼17 × 13-km crater. 4) The nature of an outcrop of thick, crudely layered, bouldery sandstone and mudstone breccia 10–20 km from the center of the impact and fractured quartz grains within its boulder clasts support its being part of the proximal ejecta blanket.